Getting the costs of environmental protection right - Lucas Bretschger (ETH Zurich, CER-ETH - Center of Economic Research, 2020)
The belief that stringent climate policies are very costly is widespread among political decision-makers and the public. The Trump administration stressed the cost argument as the motivation for the US withdrawal from the Paris Climate Agreement. However, such judgements ignore the economic benefits of policy changes and implicitly build on a misguided decomposition of environmental impacts using the IPAT and Kaya identities. The paper shows that this method predicts policy-induced income losses that are systematically and significantly biased. I extend the decomposition analysis by introducing input sub- stitution, which leads to the IPAST identity. By additionally incorporating a production approach, causal relationships between drivers of resource use, and a Romer-Kremer framework for technology development in a Schumpeterian tradition, I develop the IAT rule, a structural equation to easily estimate climate policy effects. For a given decarbonization path, I use the different rules to calculate the projected income development at the global and country level. The use of the IAT approach instead of agnostic decomposition suggests that the costs of a stringent climate policy are much lower than normally expected, which supports deep decarbonization.
Keywords: 330; environmental protection; costs of climate policy; decarbonization; IPAT identity; IAT formula